Combination of micropreparative solution isoelectric focusing and high-performance liquid chromatography for differentiation of biofilm-positive and biofilm-negative Candida parapsilosis group from vascular catheter - Vykydalová, Marie; Horká, Marie; Růžička, Filip; Duša, Filip; Moravcová, Dana; Kahle, Vladislav; Slais, Karel (Analytica chimica acta, 2014)
This study utilizes the high-performance liquid chromatography technique in combination with the new micropreparative solution isoelectric focusing fractionation on non-woven fabric strip for the characterization and differentiation of biofilm-positive and biofilm-negative forms of Candida parapsilosis sensu stricto on the basis of the changes in the composition of their cell-surface. Treatment of yeasts by boiling in distilled water relased surface substances from yeasts cells. Consequently, the optimized procedure has been used for fast identification of the highly pathogenic biofilm-positive Candida parapsilosis group in real clinical material - sonicate from vascular catheters. Moreover, the capillary isoelectric focusing was used as supporting and control technique. Obtained results suggest that this new method can be used to distinguish between biofilm-positive and negative forms of Candida parapsilosis sensu stricto.
Keywords: Electrophoresis, Polyacrylamide Gel; Chromatography, High Pressure Liquid; Capillary isoelectric focusing; Humans; elektroforéza v polyakrylamidovém gelu; Catheters, Indwelling; Sonicate from vascular catheter; zaváděcí katétry; Candida parapsilosis group; Micropreparative solution isoelectric focusing; lidé; High-performance liquid chromatography; isoelektrická fokusace; biofilmy; Biofilm; Isoelectric Focusing; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; vysokoúčinná kapalinová chromatografie; Biofilms; Candida